Statistical optimization and valuable applications of bioactive compounds produced by marine Pseudoalteromonas piscicida - Sahar Wefky Mostafa Hassan, Nermeen Ahmed El Sersy, Abeer El-Sayed Abdelwahab, Mohamed Abdel-Rahiem Ali (Journal of Applied Pharmaceutical Science, 2017)
Pseudoalteromonas piscicida was isolated from sea water in Suez Bay and identified using 16S rRNA sequence analysis. The bacterium produced compounds active against different pathogenic microbes including Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Vibrio anguillarum, Aeromonas hydrophila and Candida albicans. Plackett Burman experimental design was applied to achieve maximum production of the bioactive compounds. It achieved 1.2 fold increase when grown in medium composed of g/l: peptone, 3; beef extract, 1; inoculum size (ml), 0.5; culture volume (ml), 25 ml; sea water concentration >100 % adjusted to pH 9 and incubation period 18h at 32oC. Immobilization using adsorption technique on different support materials was applied to improve the productivity. Cells adsorbed on medical pumice realized 1.4 fold increase than the free cells. Recycling of the immobilized cells caused an increase by 1.5 fold than the free cells. Moreover, the anticancer activity of the produced compounds were tested against 4 cell lines (EI-4, Caco-2, HepG2, MCF-7). The highest activity (63.8%) was detected against Caco-2 cell line while very low activity was detected towards HepG2 and EI-4 cell lines. Antiviral activity was also studied. It succeeded to inhibit HCV replication at100 µg/ml. Another aim was to test the antioxidant activity. There was a significant antioxidant activity compared with ascorbic acid as control. Gas liquid chromatography mass spectroscopy was used to determine the major constituents in the benzene extract. It revealed the presence of 3 major compounds which are benzene,1-pentyloctyl, Benzene, 1-butylheptyl and di-n-octyl phthalate.
Keywords: Pseudoalteromonas piscicida, antibacterial,anticancer,antioxidant,Plackett Burman design, immobilization.